The personalized Berger method is usable to solve the problem of tibial rotation - Gömöri András; Gábor Németh; Csaba Zsolt Oláh; Gábor Lénárt; Zsanett Drén; Miklós Papp (Journal of Experimental Orthopaedics, 2021)
Abstract Purpose The revision of any total knee replacement is carried out in a significant number of cases, due to the excessive internal rotation of the tibial component. The goal was to develop a personalized method, using only the geometric parameters of the tibia, without the femoral guidelines, to calculate the postoperative rotational position of tibial component malrotation within a tolerable error threshold in every case. Methods Preoperative CT scans of eighty‐five osteoarthritic knees were examined by three independent medical doctors twice over 7 weeks. The geometric centre of the tibia was produced by the ellipse annotation drawn 8 mm below the tibial plateau, the sagittal and frontal axes of the ellipse were transposed to the slice of the tibial tuberosity. With the usage of several guide lines, a right triangle was drawn within which the personalized Berger angle was calculated. Results A very good intra‐observer (0.89‐0.925) and inter‐observer (0.874) intra‐class correlation coefficient (ICC) was achieved. Even if the average of the personalized Berger values were similar to the original 18° (18.32° in our case), only 70.6% of the patients are between the clinically tolerable thresholds (12.2° and 23.8°). Conclusion The method, measured on the preoperative CT scans, is capable of calculating the required correction during the planning of revision arthroplasties which are necessary due to the tibial component malrotation. The personalized Berger angle isn’t altered during arthroplasty, this way it determines which one of the anterior reference points of the tibia (medial 1/3 or the tip of the tibial tuberosity, medial border or 1/6 or 1/3 or the centre of the patellar tendon) can be used during the positioning of the tibial component. Level of evidence Level II, Diagnostic Study (Methodological Study).